Assessment of marginal sealing in indirect resin composite restorations - Batista, Graziela R.; Barcellos, Daphne C.; Torres, Carlos R.; Pucci, César R.; de Araújo, Maria M.; de Araújo, Rodrigo M. (Brazilian Dental Science, 2010)
The aim of this study was to evaluate the sealing of indirect resin restorations cemented with three different luting agents. Thirty bovine teeth were used. Box type cavities preparations were made in the middle third of the buccal face. The cavities were restored with inlay restorations by the direct/indirect technique using resin composite Resilab (Wilcos, Petrópolis, RJ, Brazil). The teeth were randomly divided into three groups: Group 1: etched with 37% phosphoric acid for 30 seconds, adhesive system Prime Bond 2.1 and Enforce resin cement (Dentsply, Petrópolis, RJ, Brazil); Group 2: etched with 37% phosphoric acid for 30 seconds, adhesive system Single Bond and RelyX ARC resin cement (3M ESPE, St Paul, MN, USA); and Group 3: resin-modified glass ionomer cement RelyX Unicem Aplicap (Dentsply, Petrópolis, RJ, Brazil). The indirect restorations were cemented with the respective cements and thermal cycled for 800 cycles. The specimens were stored in 50% silver nitrate dye for 24 hours, after this procedure the teeth were sectioned in the bucco-lingual direction into 3 slices of 1 mm thick, fixed on a glass slide and then analyzed by a stereomicroscope were was coupled a digital camera to register the images. From these pictures, the marginal leakage areas were measured by the software Image Tool 3.0. The data obtained were submitted to the ANOVA and Tukey tests. ANOVA showed that there was no significant difference (p=0.73) among groups (mean values(±SD): Group 1=0.96(±0.71); Group 2: 1.10(±0.63) and Group 3: 0.99(±0.35) . It was concluded that the 3 luting agents presented no significance regarding marginal microleakage, demonstrating similar performance in the proposed research situation.